Diagnosis, treatment, and management of pericardial effusion- review. (August 2022) - Yamani, Naser; Abbasi, Ayesha; Almas, Talal; Mookadam, Farouk; Unzek, Samuel
Abstract: The hemodynamic stability of the heart and pericardium are maintained by the pericardial fluid of volume ∼10–50 ml. Pericardial effusion is associated with the abnormal accumulation of pericardial fluid in the pericardial cavity. Numerous imaging techniques are utilized to evaluate pericardial effusion including chest X-ray, electrocardiogram, transthoracic echocardiography, computed tomography scan, cardiac magnetic resonance imaging, and pericardiocentesis. Once diagnosed, there are numerous treatment options available for the management of patients with pericardial effusion. These include various invasive and non-invasive strategies such as pericardiocentesis, pericardial window, and sclerosing therapies. In recent times, few studies have been conducted to evaluate the safety and efficacy of each approach in routine clinical practice. In this review, we review the role of different modalities in the diagnosis of pericardial effusion while highlighting existing therapies aimed at the management and treatment of pericardial effusion. Highlights: Numerous imaging techniques are utilized to evaluate pericardial effusion (PE) including chest X-ray, electrocardiogram, transthoracic echocardiography, CT scan, cardiac MRI, and pericardiocentesis. Multiple treatment options are available for the management of patients with PE including pericardiocentesis, pericardial window, and sclerosing therapies. Recent studies have evaluated the safety and efficacy of various diagnostic and management techniques in routine clinical practice. Further research is needed to investigate the optimal diagnostic and treatment options for patients with PE.